Comparing and Contrasting the Clinical Utility of Sagittal Spine Alignment Classification Frameworks: Roussouly Versus SRS-Schwab. Issue 6 (15th March 2022) - Passias, Peter G.; Bortz, Cole; Pierce, Katherine E.; Passfall, Lara; Kummer, Nicholas A.; Krol, Oscar; Lafage, Renaud; Diebo, Bassel G.; Lafage, Virginie; Ames, Christopher P.; Burton, Douglas C.; Gupta, Munish C.; et al.
Abstract : Isolated restoration of sagittal balance per the Roussouly system was not associated with superior outcomes. Patients who both matched Roussouly type and improved in Schwab modifiers had superior patient-reported outcomes at 2-years. Concurrent consideration of both systems may offer utility in establishing optimal realignment goals. Abstract : Study Design: Retrospective cohort study of a prospectively collected database. Objective: To compare clinical utility of two common classification systems for adult spinal deformity (ASD) and determine whether both should be considered in surgical planning to improve patient outcomes. Summary of Background Data: Surgical restoration of appropriate Roussouly classification shape or SRS-Schwab ASD classification may improve outcomes. Methods: ASD patients with pre- and 2-year postop (2Y) radiographic/health-related quality of life (HRQL) data were grouped by "theoretical" and "current" Roussouly type. Univariate analyses assessed outcomes of patients who mismatched Roussouly types at both pre- and 2Y intervals (Mismatched) and those of preoperative mismatched patients who matched at 2-years (Matched). Subanalysis assessed outcomes of patients who improved in Schwab modifiers, and patients who both improved in both Schwab modifiers and matched Roussouly type by 2Y. Results: Included: 515 ASD patients (59 ± 14 yrs, 80% F). Preoperative breakdown of "current" Roussouly types: Type 1 (10%), 2 (54%), 3 (24%), and 4 (12%). Matched and Mismatched groups did not differ in rates of reaching MCID for any HRQL metrics by 2Y (all P  > 0.10). Reoperation, PJK, and complications did not differ between Matched and Mismatched (all P  > 0.10), but Roussouly Matched patients had toward lower rates of instrumentation failure (17.2% vs. 24.8%, P  = 0.038). By 2Y, 28% of patients improved in PT Schwab modifier, 37% in SVA, and 46% in PI-LL. Patients who both Matched Roussouly at 2Y and improved in all Schwab modifiers met MCID for Oswestry Disability Index (ODI) and Scoliosis Research Society (SRS) activity at higher rates than patients who did not. Conclusion: Isolated restoration per the Roussouly system was not associated with superior outcomes. Patients who both matched Roussouly type and improved in Schwab modifiers had superior patient-reported outcomes at 2-years. Concurrent consideration of both systems may offer utility in establishing optimal realignment goals. Level of Evidence: 3